ELECTRICAL CONDUCTIVITY TEST IN Melanoxylon brauna SCHOTT. SEEDS (FABACEAE-CAESALPINIOIDEAE) (REVISTA DE AGRICULTURA NEOTROPICAL, 2018)
The electrical conductivity test is a simple and rapid method for evaluating seed vigor. The aim of the present study was to optimize the electrical conductivity test for assessing the vigor of Melanoxylon brauna seeds by investigating the effects of seed number (25, 50, or 75), water volume (25, 50, or 75 mL), and soaking duration (24, 48, or 72 h). The seeds belonged to two lots (I and II) that were collected in 2010 and 2012, respectively, and were incubated in a germination chamber at 25 ºC. Electrical conductivity was determined using a conductivity meter Micronal model B220. The Lot II seeds performed better, in terms of vigor and germination, than the Lot I seeds, regardless of other parameters. In addition, electrical conductivity decreased with increasing water volume and soaking duration, regardless of seed lot. In order to most effectively evaluate the physiological quality of M. brauna seed lots, the electrical conductivity test should be performed using 50 seeds, 50 mL of water, and a 48-h soaking period.